Penerapan Model Pembelajaran Praktik Berbasis Collaborative Skill Sebagai Upaya Peningkatan Mutu Pendidikan Tinggi Vokasi - Dwi Rahdiyanta; Putut Hargiyarto; Asnawi Asnawi (Jurnal Dinamika Vokasional Teknik Mesin, 2016)
This study aims to: (1) discover a collaborative skills-based learning model for practical work invocational education programs which can improve the quality of learning outcomes; (2) determine the effect ofthe application of collaborative skills-based learning model for practical work towards the students' attitude andlearning outcome. This R&D and experiments research was carried out in manufacturing industry of machiningfield in Yogyakarta, and in the Mechanical Engineering Department of Faculty of Engineering, Yogyakarta StateUniversity. The population being studied was all of Diploma students of Mechanical Engineering study programwho enrolled in Complex Machining Processes course. Research sample of 33 students, divided in two groups,were determined by purposive sampling technique. The experiment was carried out by posttest-only controldesign. Content validation was done by expert judgment and items reliability with Alpha Cronbach formula andKR-20. Data were analyzed using descriptive analysis and t-test, with significance level of 0.05. The resultsshow that: (1) The collaborative skills-based learning model for practical work is suitable to be implemented inorder to improve the quality of learning outcomes in practical work; (2) The students' attitude and learningachievement of the model class is better, or higher, than the controlled class.---------------------------------------------------------------------------------------Penelitian ini bertujuan untuk: (1) menemukan model pembelajaran praktik berbasis collaborative skillpada program pendidikan vokasi yang dapat meningkatkan kualitas hasil belajar; (2) mengetahui pengaruhpenerapan model pembelajaran praktik berbasis collaborative skill terhadap sikap dan prestasi belajarmahasiswa. Penelitian R&D dan eksperimen ini dilaksanakan di industri manufaktur bidang pemesinan diwilayah DIY dan di Jurusan Pendidikan Teknik Mesin FT-UNY. Populasi penelitian adalah seluruh mahasiswaprogram studi D3 Teknik Mesin FT-UNY yang melaksanakan kuliah Proses Pemesinan Kompleks. Pemilihansampel ditentukan dengan teknik purposive sampling. Eksperimen dilaksanakan dengan rancangan posttest-onlycontrol design. Validasi isi dilakukan dengan expert judgement dan reliabilitas butir dengan formula AlphaCronbach dan KR-20. Data dianalisis dengan analisis deskriptif dan uji-t, taraf signifikansi 0,05. Hasil penelitianmenunjukkan bahwa: (1) model pembelajaran praktik berbasis collaborative skill cocok digunakan untukmeningkatkan kualitas hasil belajar praktik; (2) Sikap dan prestasi belajar praktik mahasiswa pada kelas modellebih baik atau lebih tinggi dibanding kelas kontrol.